A paratopia do estigma: identidade e relato de si no discurso Recordações do escrivão Isaías Caminha, de Lima Barreto - Chaves, Ramon Silva (2018)
This thesis looks at paratopia of stigma and black identity in the literary discourse Recordações do Escrivão Isaías Caminha written by Lima Barreto in Brazil in 1909. Our research is based on French Discourse Analysis and predominantly on the theoretical-methodological assumptions of Dominique Maingueneau (1997;2015) about the constitutional literary discourse and literary paratopia. The main concern of this research is how the identity of the black Brazilian, an identity built under a violent system of social, economic and historical exploitation, behaves in the literary discourse Recordações do Escrivão Isaías Caminha? Our research hypothesis is that paratopia engender through stigma, a concept developed by Goffman (2012) to remodel the black identity through a historical reassessment and thus, promoting the effect of giving an account of oneself, a concept developed by Butler (2017). Our main goal is to study paratopia and use it to evaluate the construction of a black identity shaped early in the 20th century so as to become stigmatized. Our specific objective is to verify the scenographic organization and the constitution of the discursive ethos in the composition of literary paratopia in Recordações do Escrivão Isaías Caminha. Our thesis innovate when evaluating a corpus that is usually analyzed in Literature. Furthermore, it broadens the paratopia category by proposing the paratopia of stigma and associating it to ethnic-racial issues